การพัฒนาระบบวินิจฉัยมโนทัศน์ที่คลาดเคลื่อนในวิชาเคมีโดยใช้แบบสอบวินิจฉัยสามระดับร่วมกับการสะท้อนข้อมูลย้อนกลับด้วยคอมพิวเตอร์ สำหรับนักเรียนมัธยมศึกษาปีที่ 4 - สุรเดช อนันตสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This research aimed to 1) explore misconceptions in chemistry of chemical bonds of tenth-grade students, 2) develop and validate the three-tier diagnostic tests in chemical bonds, 3) develop a misconception diagnostic system in chemistry by using a three-tier diagnostic test with computer-based reflective feedback for tenth grade students and 4) validate the diagnostic system. The development was separated in three phases, i.e., exploring misconceptions; developing and validating diagnostic system; and, trying out the system and evaluating users’ satisfaction. Participants were 200 tenth-grade students for diagnostic system testing. Research instruments were interview form, two-tier diagnostic test, three-tier diagnostic test, misconception diagnostic system, system quality evaluation form, and users’ satisfaction evaluation form. Data were analyzed by using descriptive statistics, difficulty index, discrimination index, reliability and criterion-related validity. The research findings were as follows: 1. There were 40 misconceptions about chemical bonds of the tenth-grade students. The most common misconception was the fact that the net ionic equation is only written when the product is precipitated. 2. Based on Classical Test Theory (CTT) and Item Response Theory (IRT) analysis, there were 80 qualified items of three-tier diagnostic tests out of 96 items. 3. The results of the system development showed that the system design had five stages, i.e. 1) design of registration, 2) design of sequences of test and feedback, 3) design of screen, 4) design of test reports, and 5) design of system manual. There were three steps in the developed system, i.e., 1) testing registration, 2) testing, and 3) reporting the test results. 4. It was found that the experts suggested that the system is suitable in all four aspects. The quality of the system design and system performance were in the highest level. In addition, the system evaluation after trying out session revealed that the most satisfying thing for the student was the easy-to-use and smooth running of the system.